LOCAL WISDOMIN LEARNING AS AN EFFORT TO INCREASE CULTURAL KNOWLEDGE: STUDENTS’ PERCEPTION AS PROSPECTIVE TEACHERS - Pamenang, Fransisca Ditawati Nur (Sanata Dharma University Yogyakarta, 2021)
Education not only teaches concepts but also the formation of attitudes and characters in preserving local culture. Knowledge of local wisdom is important because it is a means for students to better understand and love their culture. This study aims to determine the response of students and how the ability of prospective teachers to design local wisdom-based learning. A questionnaire and observation instrument were employed in this research. Students' perceptions of learning based on local wisdom were assessed. Besides, the ability of students in designing local wisdom-based learning activities was evaluated. This type of research is a qualitative descriptive study. The results of this research showed students' positive perception of learning based on local wisdom. The ability of students in designing learning activities gives good results. Local wisdom-based learning provides an opportunity for students to get to know their local culture and develop it into chemistry learning activities. The researcher of this study suggests the continuity of the implementation of local wisdom-based learning to preserve local wisdom values.